2015
DOI: 10.1007/s10826-015-0124-8
|View full text |Cite
|
Sign up to set email alerts
|

The Distress of Citizen-Children with Detained and Deported Parents

Abstract: In immigration enforcement, many undocumented immigrants with children are often detained and deported. But it is their US-born citizen-children that have been overlooked in immigration debates and enforcement policies and practices. Citizen-children are at risk for negative psychological outcomes when families are fractured and destabilized by arrest, detention, and deportation. The children risk being torn from their parents and, often, their undocumented siblings. To add to the small but growing empirical b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(97 citation statements)
references
References 28 publications
4
91
0
2
Order By: Relevance
“…An estimated 4.5 million U.S. citizen children live in families in which one or both parents are undocumented (Pew Hispanic Research Center, ). A growing body of literature has begun to document the link between parental detention and deportation and Latino children's trauma and psychological distress (Allen, Cisneros, & Tellez, ; Brabeck, Lykes, & Hunter, ; Rojas‐Flores et al., ; Zayas, Aguilar‐Gaxiola, Yoon, & Rey, ). This review paper adds to the literature by proposing that the persistent threat of parental deportation and chronic uncertainty regarding familial safety is also harmful to Latino children and youth, especially those living in mixed‐status households, and is experienced by many children as a form of psychological violence.…”
Section: Concluding Remarks and Recommendationsmentioning
confidence: 99%
“…An estimated 4.5 million U.S. citizen children live in families in which one or both parents are undocumented (Pew Hispanic Research Center, ). A growing body of literature has begun to document the link between parental detention and deportation and Latino children's trauma and psychological distress (Allen, Cisneros, & Tellez, ; Brabeck, Lykes, & Hunter, ; Rojas‐Flores et al., ; Zayas, Aguilar‐Gaxiola, Yoon, & Rey, ). This review paper adds to the literature by proposing that the persistent threat of parental deportation and chronic uncertainty regarding familial safety is also harmful to Latino children and youth, especially those living in mixed‐status households, and is experienced by many children as a form of psychological violence.…”
Section: Concluding Remarks and Recommendationsmentioning
confidence: 99%
“…The health implications of these circumstances are revealed in a small but growing body of research documenting differences in the health and well-being of children in varying legal statuses and with different experiences of immigration enforcement. The most severe of these is arguably experiencing a parent's deportation, and indeed, studies find that the deportation of a parent has profound and long-lasting psychological consequences for spouses and children left behind (Allen, Cisneros, & Tellez, 2015;Chaudry et al, 2010;Dreby, 2012;Hagan et al, 2009;Zayas, Aguilar-Gaxiola, Yoon, & Rey, 2015). One study, for example, found that children whose parents had been deported were significantly more likely to present externalizing and internalizing behavior problems than similar children with unauthorized parents not facing deportation (Allen et al, 2015).…”
Section: Policies That Undermine Health and Health Carementioning
confidence: 99%
“…For example, growing evidence documents the negative health consequences of parental detention or deportation (and threats of such enforcement action) on citizen children (Brabeck & Xu, 2010;Rojas-Flores et al, 2017;Zayas & Gulbas, 2017;Ybarra & Peña, 2017). And a burgeoning literature on citizen children who leave the United States to be raised in their parents' countries of origin shows that these children struggle to overcome a host of linguistic, social, and educational challenges (Dreby, 2012;Medina & Menjívar, 2015;Zayas et al 2015;Hernández-León & Zúñiga, 2016). Beyond challenges faced by citizen children in their initial transition to life in their parents' countries of origin, much less is known about their long-term outcomes and experiences.…”
Section: Deportation Of Immigrant Parents With Us Citizen Childrenmentioning
confidence: 99%